The Role of Thoracic Ultrasound in Diagnosing Pneumothorax - Mia Elhidsi; Budhi Antariksa; Dianiati Kusumo Sutoyo (Jurnal Respirologi Indonesia, 2018)
Diagnosis of a pneumothorax in some cases the can be difficult. Traditional gold-standard modalities may not be available or feasible to institute. In this situation, thoracic sonography for pneumothorax can be especially helpful, allowing a method of quickly ruling out this potentially life-threatening complication. Its sensitivity dan specificity of ultrasound is higher than conventional chest x-ray. The four sonograms useful to diagnose pneumothorax and their usefulness in ruling in and ruling out the condition are lung sliding, lung pulse, B-lines and lung point. (J Respir Indo. 2018; 38: 239-43)